2021
DOI: 10.1111/jfpp.15960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aloe vera gel‐based active coating incorporated with catechin nanoemulsion and calcium chloride on postharvest quality of fresh strawberry fruit

Abstract: This study was aimed to investigate the effect of edible coating based on Aloe vera containing free and encapsulated catechin (0% and 5%) and calcium chloride (0% and 2%) on the postharvest quality of strawberry (Fragaria vesca L.) under cold storage.The physicochemical and qualitative characteristics of strawberries, including pH, titratable acidity, total soluble solids, vitamin C, antioxidant properties, total phenol, total yeast and mold counts, total anthocyanins, and firmness, were measured under refrige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…One of the most famous soluble salt forms of calcium is CaCl 2 . Previous research has shown that calcium plays a role in the quality and the shelf-life of several vegetable crops, including cucumber [ 19 ] and strawberry [ 20 ]. Moreover, the application of calcium chloride after harvest delays the progress of ripening, reduces decay, and increases the calcium level in treated fruits, resulting in higher nutritional value in treated fruits [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%